Human Development Index and Multidimensional Poverty Index: Evidence on their Reliability and Validity - Beja, Edsel L, Jr (Archīum Ateneo, 2021)
The paper tests the reliability and the validity of the Human Development Index (HDI) from the United Nations Develop-ment Programme and the Multidimensional Poverty Index (MPI) from the Oxford Poverty & Human Development Initia-tive. The results indicate that there is strong reliability within metric; and that there is strong validity between metrics. The findings imply that both HDI—more specifically; the inverse; (1-HDI)—and MPI embody equivalent descriptions about the level of human development or the lack of it.